Upaya Guru BK dalam Mencegah Perilaku Bullying di SMA N 1 Candung - Rahmi Rahmi; Afrinaldi Afrinaldi; Linggana Tesya (Badan Penerbit STIEPARI Press, 2024)
All humans are born in good condition, with intelligence that differentiates them from other creatures. The human mind needs to be directed so that it can function well, the way to direct it is through education. Education is an effort made to shape patterns of human behavior that should be, develop developmental tasks that must be completed, and produce human resources through the learning process of attitudes, knowledge and skills. The learning process refers to the reciprocal relationship carried out by a teacher with a group of students until they achieve a specified qualification. Competency performance can be seen in the results of educating students with learning outcomes and implementation that are very large for the child's future, namely the impact of these learning results. A problem that often occurs in the world of education is that students who feel they are smart, great, strong, physically, have a high social strata, and are economically above average tend to embarrass, enslave and abuse their friends.